Basement structure and its influence on the structural configuration of the northern North Sea rift. Issue 6 (29th June 2017) - Fazlikhani, Hamed; Fossen, Haakon; Gawthorpe, Robert L.; Faleide, Jan Inge; Bell, Rebecca E.
Abstract: The northern North Sea rift basin developed on a heterogeneous crust comprising structures inherited from the Caledonian orogeny and Devonian postorogenic extension. Integrating two‐dimensional regional seismic reflection data and information from basement wells, we investigate the prerift structural configuration in the northern North Sea rift. Three seismic facies have been defined below the base rift surface: (1) relatively low‐amplitude and low‐frequency reflections, interpreted as pre‐Caledonian metasediments, Caledonian nappes, and/or Devonian clastic sediments; (2) packages of high‐amplitude dipping reflections (>500 ms thick), interpreted as basement shear zones; and (3) medium‐amplitude and high‐frequency reflections interpreted as less sheared crystalline basement of Proterozoic and Paleozoic (Caledonian) origin. Some zones of Seismic Facies 2 can be linked to onshore Devonian shear zones, whereas others are restricted to the offshore rift area. Interpreted offshore shear zones dip S, ESE, and WNW in contrast to W to NW dipping shear zones onshore West Norway. Our results indicate that Devonian strain and ductile deformation was distributed throughout the Caledonian orogenic belt from central South Norway to the Shetland Platform. Most of the Devonian basins related to this extension are, however, removed by erosion during subsequent exhumation. Basement shear zones reactivated during the rifting and locally control the location and geometry of rift depocenters, e.g., in the Stord and East Shetland basins. Prerift structures with present‐day dips >15° were reactivated, although some of the basement shear zones are displaced by rift faults regardless of their orientation relative to rift extension direction. Key Points: Devonian postorogenic shear zones dip in various directions with <40 degrees in the northern North Sea rift, central part of the Caledonian orogenic belt Shear zones with present‐day dips higher than ~15° were reactivated during the late Paleozoic‐Mesozoic rift events Several basement shear zones have been offset by rift‐related faults regardless of their orientation relative to the rift extension direction